Spatial genome exploration in the context of cognitive and neurological disease. (December 2019) - Rajarajan, Prashanth; Borrman, Tyler; Liao, Will; Espeso-Gil, Sergio; Chandrasekaran, Sandhya; Jiang, Yan; Weng, Zhiping; Brennand, Kristen J; Akbarian, Schahram
Highlights: Review of Hi-C genome-scale chromosome conformation ('3D Genome') mappings in brain. Discussion of developmental 3DG reorganization in differentiating neurons. Discussion of chromosomal contacts associated with schizophrenia risk sequences. Monogenic neurological disorders and DNA repeats at chromatin domain boundaries. Abstract : The 'non-linear' genome, or the spatial proximity of non-contiguous sequences, emerges as an important regulatory layer for genome organization and function, including transcriptional regulation. Here, we review recent genome-scale chromosome conformation mappings ('Hi-C') in developing and adult human and mouse brain. Neural differentiation is associated with widespread remodeling of the chromosomal contact map, reflecting dynamic changes in cell-type-specific gene expression programs, with a massive (estimated 20–50%) net loss of chromosomal contacts that is specific for the neuronal lineage. Hi-C datasets provided an unexpected link between locus-specific abnormal expansion of repeat sequences positioned at the boundaries of self-associating topological chromatin domains, and monogenic neurodevelopmental and neurodegenerative disease. Furthermore, integrative cell-type-specific Hi-C and transcriptomic analysis uncovered an expanded genomic risk space for sequences conferring liability for schizophrenia and other cognitive disease. We predict that spatial genome exploration will deliver radically new insights into the brain nucleome in health and disease.